Field reports form for submitting seasonal observations of Iowa birds, Jim Sinclair, fall 1994 - Sinclair, Jimet al (1994)
An annotated list of birds sighted by Jim Sinclair. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed